The Impact of an Infectious Diseases Transition Service on the Care of Outpatients on Parenteral Antimicrobial Therapy. (October 2013) - Keller, Sara C.; Ciuffetelli, Danielle; Bilker, Warren; Norris, Anne; Timko, Daniel; Rosen, Alex; Myers, Jennifer S.; Hines, Janet; Metlay, Joshua
Background: Many hospitalized patients with complicated infections are discharged on outpatient parenteral antimicrobial therapy (OPAT). However, little is known about how to improve the postdischarge care of OPAT patients.Objective: The impact of an infectious diseases transitions service (IDTS) on OPAT patient readmissions, as well as on processes of care, was evaluated.Methods: We performed a controlled, quasi-experimental evaluation over 15 months in an academic medical center. Intervention-arm patients, before and after the introduction of an IDTS, were seen by the general infectious diseases consult teams, while control-arm patients (discharged on OPAT after hospitalization with bacteremia) were not. The IDTS prospectively tracked all OPAT patients and coordinated follow-up. The impact of the IDTS was calculated using a differences-in-differences approach where the interaction between time (before vs after the IDTS intervention) and study arm (intervention vs control arm) was the variable of interest. The control arm was used only in primary outcome analyses (readmissions and emergency department visits). Secondary outcomes included process of care measures and non-readmission clinical outcomes.Results: Of 488 consecutive patients requiring OPAT, 362 were in the intervention arm (215 pre-intervention and 147 post-intervention) and 126 in the control arm (70 pre-intervention and 56 post-intervention). Compared to the control arm, the IDTS was not associated with changes in 60-day readmissions and/or emergency department visits (adjusted odds ratio [OR] = 0.48; 95% confidence interval [CI] = 0.13-1.79). In the intervention arm, implementation of the IDTS was associated with fewer antimicrobial therapy errors (OR = 0.062; 95% CI = 0.015-0.262), increased laboratory test receipt (OR = 27.85; 95% CI = 12.93-59.99), and improved outpatient follow-up (OR = 2.44; 95% CI = 1.50-3.97).Conclusions: In a controlled evaluation, the IDTS did not affect readmissions despite improving process of care measures for targeted patients. Care coordination services may improve OPAT quality of care, but their relationship to readmissions is unclear.